Recovery of Flavor Components from Blue Crab Processing Wastewater By Reverse Osmosis Technology - Uju B Ibrahim; W Trilaksani; T Nurhayati; B Riyanto (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2008)
The waste water of blue crab pasteurization is potential to cause environmental pollution. It contained TSS 206.5 mg/L, BOD 7,092.6 mg/L and COD 51,000 mg/L. However the was the water also contains an interesting flavor compounds, which composed of 0.23% non protein nitrogen and 17 amino acids with the highest being glutamic acid. In this work, pre-filtration steps using filter of 0.3 Ã‚Âµ size followed by reverse osmosis has been used to reduce these pollutions load and recover the flavor compound. During pre-filtration steps, TSS was reduced to 74.8% so the turbidity increased up to 31%. After reverse osmosis process, BOD, and COD were decreased more than 99%, and there was no amino acids detected in the permeate stream. Factors that affect performance of reverse osmosis were transmembrane pressure, temperature and pH. Higher transmembrane pressure, temperature and pH resulted in the higher permeate flux. Key word : blue crab, flavor, reserve osmosis